Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011 International Symposium on Empirical Software Engineering and Measurement 2011
DOI: 10.1109/esem.2011.25
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of Textual and Graphical Representations for Software Architecture Design

Abstract: Software architecture design documentation should communicate design decisions effectively. However, little is known about the way recipients respond to the different types of media used in documentation. We therefore conducted a controlled experiment to study whether visual or textual artifacts are more effective in communicating architecture software design decisions to software developers. Our participant group consisted of 47 participants from both industry and academia. Our results show that neither diagr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
(25 reference statements)
2
24
1
Order By: Relevance
“…Recently, Heijstek [2] et al reported findings pointing to the fact that neither textual nor graphical representations were significantly effective for understanding a software architecture. They also reported that the more experienced subjects, mostly, preferred textual representations.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Heijstek [2] et al reported findings pointing to the fact that neither textual nor graphical representations were significantly effective for understanding a software architecture. They also reported that the more experienced subjects, mostly, preferred textual representations.…”
Section: Related Workmentioning
confidence: 99%
“…Heijstek et al [2] adopted this measure to investigate whether the difference between their subjects' native language and English can impact their efficiency and accuracy while understanding a model. In this paper, we are also interested to investigate if the distance of our subjects' native language from English can impact our findings.…”
Section: Dependent Independent and Mitigating Variablesmentioning
confidence: 99%
See 3 more Smart Citations